2013
DOI: 10.1007/s12032-013-0506-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated thyroid carcinoma: comparison of histopathologic characteristics, clinical course, and outcome between young children and adolescents

Abstract: Differentiated thyroid carcinoma is rare in patients younger than 21 years, especially in children, but it is associated with a greater risk of metastases and recurrence. The aim of our study was to compare the characteristics, clinical course, and outcome of the disease between young children (≤16 years) and adolescents (17-21 years). We reviewed the medical records of 62 young children and adolescents (47 females, 15 males, ≤21 years) with DTC who were diagnosed between 1990 and 2010 and admitted for radioio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…There are significant distinctions in this cohort in terms of the pres- In contrast to other recent analyses, 14,15,17 we did not identify a difference in the rates of central or lateral neck LN metastases; however, the lymph node ratio was higher in children <12. A lymph node ratio >0.42 has previously been demonstrated, in an adult cohort, to be associated with elevated recurrence risk.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There are significant distinctions in this cohort in terms of the pres- In contrast to other recent analyses, 14,15,17 we did not identify a difference in the rates of central or lateral neck LN metastases; however, the lymph node ratio was higher in children <12. A lymph node ratio >0.42 has previously been demonstrated, in an adult cohort, to be associated with elevated recurrence risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite a rising incidence of paediatric thyroid cancer, few studies have defined the differences in thyroid cancer in children as a function of age . Recent American Thyroid Association (ATA) Guidelines for Management of Children with Thyroid Nodules and Differentiated Thyroid Cancer acknowledge that “it remains unclear if younger children (<10‐15 years of age) are at greater risk for more extensive disease or higher rates of recurrence.” Younger children may have more extensive and aggressive disease at presentation or may harbour occult disease that surfaces following primary therapy . In one study, younger children received higher cumulative doses of radioactive iodine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid carcinoma is rare in children and adolescents, which accounts for 0.5%–3% ( 9 ), but the occurrence has been rising recently. Children and adolescents with PTC have unique biological characteristics; it has been proposed in the literature that they are more likely to have stronger invasiveness, higher LNM, and recurrence rate ( 10 , 11 ). Therefore, it is necessary to do further research on the clinicopathological characteristics and prognosis of this age group to provide evidence for the clinical development of diagnosis and treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…The biological behavior of pediatric thyroid cancer is known to be different from that in adult patients; it has been suggested that it presents at a more advanced stage in prepuberty than in puberty ( 17 ). Younger pediatric patients are associated with a larger mean tumor size, more aggressive pathological features, and higher incidence of loco-regional and distant metastasis ( 18 , 19 ). The patients first presented with symptoms such as neck swelling with a palpable mass or discomfort ( 3 , 20 ).…”
Section: Introductionmentioning
confidence: 99%